The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

A new foundation for the study of bird behaviour: Konrad Lorenz’s ‘Kumpan’ paper of 1935 - Tim Birkhead; Karl Schulze-Hagen (Journal of Ornithology, 2024)
The Nobel Prize in Physiology or Medicine was awarded to Konrad Lorenz, Niko Tinbergen and Karl von Frisch in 1973 for their pioneering work during the 1930s and 1940s, in the study of animal behaviour. Lorenz established the foundations of ethology in 1935 in what has become known as his “Kumpan paper”. The paper focussed on the social relationships between conspecifics (i.e. ‘kumpans’, companions) and provided a much-needed conceptual framework for the study of animal behaviour. We describe the origins and immediate reception of Lorenz’s paper using his correspondence with colleagues, mainly Erwin Stresemann who was then the influential editor of Journal für Ornithologie . The Kumpan paper was notable for its extraordinary originality, but also for its length and—in parts—its incomprehensible language. Most of Lorenz’s concepts were rapidly superseded as the field of Ethology/Animal Behaviour developed over the following decades. The paper (translated in full into English only in 1970) is rarely read today, but as we show, many of Lorenz’s observations of birds are both timeless and highly original and have the potential to inspire further research today.

Egg shape in the Common Guillemot Uria aalge and Brunnich’s Guillemot U. lomvia: not a rolling matter? - Tim R. Birkhead; Jamie E. Thompson; John D. Biggins (Journal of Ornithology, 2017)

Seasonal variation in ejaculate traits of male red-winged blackbirds (Agelaius phoeniceus) - Stefan Lüpold; Tim R. Birkhead; David F. Westneat (Behavioral Ecology and Sociobiology, 2012)

Genetic mapping of the major histocompatibility complex in the zebra finch (Taeniopygia guttata) - Robert Ekblom; Jessica Stapley; Alex D. Ball; Tim Birkhead; Terry Burke; Jon Slate (Immunogenetics, 2011)

Geographical variation in sperm morphology in the red-winged blackbird (Agelaius phoeniceus) - Stefan Lüpold; David F. Westneat; Tim R. Birkhead (Evolutionary Ecology, 2011)

On the use of large marker panels to estimate inbreeding and relatedness: empirical and simulation studies of a pedigreed zebra finch population typed at 771 SNPs - ANNA W. SANTURE; JESSICA STAPLEY; ALEXANDER D. BALL; TIM R. BIRKHEAD; TERRY BURKE; JON SLATE (Molecular Ecology, 2010)
In recent years there has been a dramatic increase in the availability of high density genetic marker data for both model and non‐model organisms. A potential application of these data is to infer relatedness in the absence of a complete pedigree. Using a marker panel of 771 SNPs genotyped in three generations of an extensive zebra finch pedigree, correlations between pedigree relatedness and seven marker‐based estimates of relatedness were examined, as was the relationship between heterozygosity and inbreeding. Although marker‐based and pedigree relatedness were highly correlated, the variance in estimated relatedness was high. Further, the correlation between heterozygosity and inbreeding was weak, even though mean inbreeding coefficient is typical of that seen in wild vertebrate pedigrees; the weak relationship was in part due to the small variance in inbreeding in the pedigree. Our data suggest that using marker information to reconstruct the pedigree, and then calculating relatedness from the pedigree, is likely to give more accurate relatedness estimates than using marker‐based estimators directly.

Sperm design and variation in the New World blackbirds (Icteridae) - Stefan Lüpold; George M. Linz; Tim R. Birkhead (Behavioral Ecology and Sociobiology, 2009)

Reproductive biology of the European Cuckoo Cuculus canorus: early insights, persistent errors and the acquisition of knowledge - Karl Schulze-Hagen; Bard G. Stokke; Tim R. Birkhead (Journal of Ornithology, 2009)

Impaired hatching success and male-biased embryo mortality in Tree Sparrows - Magnus Svensson; Pekka T. Rintamäki; Tim R. Birkhead; Simon C. Griffith; Arne Lundberg (Journal of Ornithology, 2007)

Oil pollution and climate have wide‐scale impacts on seabird demographics - Stephen C. Votier; Ben J. Hatchwell; Andrew Beckerman; Robin H. McCleery; Fiona M. Hunter; Jayne Pellatt; Mark Trinder; Tim R. Birkhead (Ecology Letters, 2005)
Oil spills often spell disaster for marine birds caught in slicks. However, the impact of oil pollution on seabird population parameters is poorly known because oil spills usually occur in wintering areas remote from breeding colonies where birds may be distributed over a wide area, and because it is difficult to separate the effects of oil pollution from the effect of natural environmental variation on seabird populations. Using a long‐term data set we show that over‐winter survival of adult common guillemots ( Uria aalge ) is negatively affected by both the incidence of four major oil‐spills in their wintering grounds and high values of the North Atlantic Oscillation (NAO) index. After controlling for the effect of the NAO index, we show that winter mortality of adult guillemots is doubled by major oil pollution incidents. Our results demonstrate that oil pollution can have wide‐scale impacts on marine ecosystems that can be quantified using populations of marked individuals to estimate survival.

Patterns of courtship behavior and ejaculate characteristics in male red-winged blackbirds - David F. Westneat; Lisa A. McGraw; Jennifer M. Fraterrigo; Tim R. Birkhead; F. Fletcher (Behavioral Ecology and Sociobiology, 1998)